Derivative free method for computing modes of multilayer planar waveguide - Semwal, Girish; Rastogi, Vipul (Optical and quantum electronics, 2014)
A technique to solve generalized dispersion equation of multilayer planar waveguide has been demonstrated to obtain all the expected guided modes. The solution is based on the derivative free method for computing the zeros of an analytical function in complex plane. The derivative free method extracts the roots which are very close to actual zeros of the function. Roots are further refined using the robust iteration method to achieve the desired accuracy. Application of the proposed method has been verified by solving the modes of a variety of structures including lossless structure, leaky structure, quantum well waveguide, active waveguide, ARROW waveguide and metal clad waveguide. The method is efficient and computes all modes of planar waveguide with high accuracy.